Mortality among healthcare workers in Indonesia during 18 months of COVID-19. - Lenny L Ekawati; Ahmad Arif; Irma Hidayana; Ahmad Nurhasim; M Zakiyuddin Munziri; Karina D Lestari; Amanda Tan; Firdaus Ferdiansyah; Fikry Nashiruddin; Qorinah E S Adnani; Halik Malik; Tri Maharani; et al. (Public Library of Science (PLoS), 2022)
The impact of SARS-CoV-2 infections upon Indonesian health care workers (HCWs) is unknown due to the lack of systematic collection and analysis of mortality data specific to HCWs in this setting. This report details the results of a systematic compilation, abstraction and analysis of HCW fatalities in Indonesia during the first 18 months of COVID-19. HCW who passed away between March 2020 and July 2021 were identified using Pusara Digital, a community-based digital cemetery database dedicated to HCW. We calculated the mortality rates and death risk ratio of HCWs versus the general population. The analysis indicates that at least 1,545 HCWs died during the study period. Death rates among males and females HCWs were nearly equivalent (51% vs. 49%). The majority were physicians and specialists (535, 35%), nurses (428, 28%), and midwives (359, 23%). Most deaths occurred between the ages of 40 to 59 years old, with the median age being 50 years (IQR: 39-59). At least 322 deaths (21%) occurred with pre-existing conditions, including 45 pregnant women. During the first 18 months of COVID-19 in Indonesia, we estimated a minimum HCW mortality rate of 1.707 deaths per 1,000 HCWs. The provincial rates of HCW mortality ranged from 0.136 (West Sulawesi) to 5.32 HCW deaths per 1,000 HCWs (East Java). The HCW mortality rate was significantly higher than that of the general population (RR = 4.92, 95% CI 4.67-5.17). The COVID-19 pandemic in Indonesia resulted in the loss of many hundreds of HCWs, the majority of whom were senior healthcare workers. The HCW mortality rate is five times that of the general population. A national systematic surveillance of occupational mortality is urgently needed in this setting.